2019
DOI: 10.1111/ajt.15353
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of low risk for dropout from the liver transplant waiting list for hepatocellular carcinoma in long wait time regions: Implications for organ allocation

Abstract: All patients with hepatocellular carcinoma meeting United Network for Organ Sharing T2 criteria currently receive the same listing priority for liver transplant (LT).A previous study from our center identified a subgroup with a very low risk of waitlist dropout who may not derive immediate LT benefit. To evaluate this issue at a national level, we analyzed within the United Network for Organ Sharing database 2052 patients with T2 hepatocellular carcinoma receiving priority listing from 2011 to 2014 in long wai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…These results are similar to a previous analysis from our center that showed that patients with a single, small 2‐ to 3‐cm tumor and low AFP level less than 20 ng/mL who had a complete response to LRT (20% of cohort) have a very low risk of wait‐list dropout, and thus likely derive minimal short‐term benefit from LT. Finally, an analysis of the United Network of Organ Sharing (UNOS) database found that a combination of tumor (single lesion 2‐3 cm and AFP < 20 ng/mL) and liver‐related characteristics (Child A cirrhosis and MELD–sodium [MELD‐Na] < 15) identifies a subgroup with a low wait‐list dropout risk. Taken together, patients with compensated liver disease and relatively minimal tumor burden who have a low AFP level and complete response to LRT have a long wait‐list life expectancy, and thus optimal LT criteria should reduce (or eliminate) priority for these patients.…”
Section: Transplant Survival Benefit and Identifying Patients With Hcmentioning
confidence: 99%
“…These results are similar to a previous analysis from our center that showed that patients with a single, small 2‐ to 3‐cm tumor and low AFP level less than 20 ng/mL who had a complete response to LRT (20% of cohort) have a very low risk of wait‐list dropout, and thus likely derive minimal short‐term benefit from LT. Finally, an analysis of the United Network of Organ Sharing (UNOS) database found that a combination of tumor (single lesion 2‐3 cm and AFP < 20 ng/mL) and liver‐related characteristics (Child A cirrhosis and MELD–sodium [MELD‐Na] < 15) identifies a subgroup with a low wait‐list dropout risk. Taken together, patients with compensated liver disease and relatively minimal tumor burden who have a low AFP level and complete response to LRT have a long wait‐list life expectancy, and thus optimal LT criteria should reduce (or eliminate) priority for these patients.…”
Section: Transplant Survival Benefit and Identifying Patients With Hcmentioning
confidence: 99%
“…( 31‐36 ) Patients with well‐compensated disease and a single, small, well‐treated tumor (approximately 20% of listed HCC patients ( 36 ) ) most likely derive less benefit from receiving a DCD donor graft because that population can either wait for a standard criteria donor or perhaps avoid LT altogether (until tumor recurrence). ( 35 ) At the other extreme, in patients with high risk of HCC recurrence (eg, AFP at LT >100 ng/mL, progressive disease after LRT, or a RETREAT score >4), ( 37,38 ) the present findings suggest DCD livers worsen patient and graft survival. On one hand, these patients actually have a large mortality benefit from accepting an early offer DCD liver rather than waiting for a superior DBD liver because these patients are at high risk of wait‐list dropout and/or death.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the introduction of policies that allow greater equity in the access to DDLT between these 2 groups of patients, with and without HCC, is extremely necessary. UNOS has adopted the policy of not assigning any special scores to HCC patients in the first six months on the list, but other allocation suggestions can and should be evaluated to be eventually used in Brazil (12,(31)(32)(33) .…”
Section: Discussionmentioning
confidence: 99%